Morphological Changes of the Frontal Sinus with Age a Two-dimensional Geometric Morphometric Study - Nur Damia Iwani Zulkiflee; Mansharan Kaur Chainchel Singh; Aspalilah Alias; Helmi Hadi; Eric Chung; Nurul Hannim Zaidun; Rani Sakaran; Ker Woon Choy (Elsevier, 2024)
Indexed by WOS/Scopus